A comparison between finite element analysis code and cosmos software - S. Hamid, Bilal (2005)
In order to fulfill various needs of different users in different applications, there must exist a mutual understanding between software house and the users. The software developers should know exactly what the users need in their work and the developed software should perform accordingly. The users could come from any discipline, and the designers and the engineers are amongst those. In this project, a study has been carried out to compare the effectiveness between COSMOS software and the finite element generated programming code in order to do stress analysis on 3D object. In this study, the amount of stress will be imposed on subject area, and the resulted effect will be visualized as a gradual changed of colors. The engineers and designers will benefit from this study in terms of increasing their skill in design and obtain a well defined design since the competition become higher day after day.